Exporting construction services to West Africa: a study of Nigerian firms’ resources and capabilities - Odediran, Sunday Julius; Ojo, Grace Kehinde; Oladunmoye, Funmilola Ruth; Bayo-Adegoke, Esther Adefunmilola (Frontiers in Built Environment, 2025)
IntroductionThe Nigerian construction industry has experienced significant growth in recent years, driven by government investments in infrastructures and a surge in private sector activities. This led to the emergence of construction organizations with enhanced capabilities, positioning them for expansion beyond the domestic market, hence this study. This paper examines the resources and capabilities of construction organizations in Nigeria to export their services across borders into West African countries with a view to minimizing economic loss in the region.MethodWith a quantitative research approach, a well-structured questionnaire was employed to collect data from 103 construction organizations including eight architectural, 47 engineering, nine estate surveying and valuation, 22 quantity surveying; and 17 contracting firms located in Lagos and Abuja. Data reported in this paper were analyzed using mean score, analysis of variance and factor analysis.ResultsThe results revealed that the top ranked resources and capabilities ranked as significant requirement for exporting services into West African markets is business reputation and trust (M = 4.04). This is followed by human capital (M = 3.94), organizational and operational structure (M = 3.94) and information about a market (M = 3.87).Discussion/ConclusionThe study concludes that reputation, trust, personnel, organization structure and market information are essential requirements for construction organizations to export services into the West African markets.